(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
This study explores the complex interactions between soil ecosystems and olive oil industry outputs, with an emphasis on waste from olive mills. Employing a multi-faceted approach encompassing field experiments and advanced laboratory analyses, our study discerns the nuanced impact of olive pomace and wastewater on the biological tapestry of soil. By meticulously scrutinizing alterations in microbial communities and soil nutrient dynamics, we aim to unravel the ecological ramifications of olive oil industry waste disposal. Our investigation not only catalogues the distinctive composition of these waste components but also elucidates their consequential effects on the microbial composition and nutrient richness of soil. Employing cutting-edge DNA sequencing techniques, we explore the subtleties of microbial diversity and abundance shifts, providing a comprehensive understanding of the intricate symbiosis within soil ecosystems. Furthermore, statistical analyses unravel correlations between waste constituents and soil biological properties, elucidating critical insights for sustainable agricultural practices. The results of this study not only broaden our understanding of the ecological consequences of waste from the olive oil business, but they also provide useful suggestions for reducing any possible negative impacts. This research highlights the need of sustainable waste disposal methods in maintaining the health of our agricultural landscapes and acts as a guide for knowledgeable soil management techniques.